Performance of Membrane Biological Reactor for Tobacco Wastewater Treatment - Alhajar, Abdallah Hazim Abdallah (2023)
A Master of Science thesis in Chemical Engineering by Abdallah Hazim Abdallah Alhajar entitled, “Performance of Membrane Biological Reactor for Tobacco Wastewater Treatment”, submitted in April 2023. Thesis advisor is Dr. Sameer Al-Asheh and thesis co-advisor is Dr. Ahmed Aidan. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).